2014
DOI: 10.5194/nhess-14-3195-2014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of extreme wave events on the southern coast of Brazil

Abstract: Abstract. Using the wave model SWAN (simulating waves nearshore), high waves on the southwestern Atlantic generated by extra-tropical cyclones are simulated from 2000 to 2010, and their impact on the Rio Grande do Sul (RS) coast is studied. The modeled waves are compared with buoy data and good agreement is found. The six extreme events in the period that presented significant wave heights above 5 m, on a particular point of interest, are investigated in detail. It is found that the cyclogenetic pattern betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 14 publications
2
22
0
1
Order By: Relevance
“…Rusu, 2011). Recent SWAN short-term applications on the SBS are found in Cuchiara et al (2009) and Guimarães et al (2014).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Rusu, 2011). Recent SWAN short-term applications on the SBS are found in Cuchiara et al (2009) and Guimarães et al (2014).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…The wave model used as the base of this operating system is the MF-WAM. This model is based on the IFS-ECWAM (cycle 38R2) code, with changes according to dissipation by the wave breaking and the swell damping source terms as developed in Ardhuin et al As previous works have unequivocally revealed the importance of rigorous validation of operational wave forecasting systems [3,4] and the analysis of extreme wave height events using models [5,6] and shore-based high-frequency radar (HFR) [7,8], the objectives of this paper were twofold. The first objective was to analyze the main features of extreme wave height events in Galicia over the wintertime of a two-year period (2015-2016) by using HFR remote-sensed hourly wave parameters in tandem with predictions from an operational wave (WAV) forecasting system running in the Iberia-Biscay-Ireland (IBI) area, denominated IBI-WAV (Figure 1b).…”
Section: The Iberia-biscay-ireland Wave (Ibi-wav) Operational Forecasmentioning
confidence: 99%
“…Guimarães et al 2014) but not in the Baltic Sea. Although there were several studies focused on the modelling of wave field in this region (e.g.…”
Section: Introductionmentioning
confidence: 87%